Children Have Faced Several Challenges: Analyzing Reports of Children Who Became Orphans Caused by COVID-19 - Sarah Madinatu Hassan (Ilomata International Journal of Social Science, 2022)
Many children have become orphans due to COVID-19. Their experiences have been under reported due to focus on other areas. This study explores adverse social consequences of children who became orphans due to COVID-19. With the aid of a documentary review approach, this study extracts and analyzes reports from 11 highly ranked news reporting sites in the United States of America that contained expert opinions and narratives on the negative social consequences of being orphaned by COVID-19. Analysis of data followed the narrative thematic analysis procedure. The outstanding themes identified are the loss of caregivers and primary social support system, and increased risk of mental health concerns. The findings demonstrate the need for emergency financial support for COVID-19 related orphaned children and the involvement of experts trained in Trauma-Focused Cognitive-Behavior Therapies (TF-CBT) to help children’s psychosocial needs.